Investigation of the distribution and antifungal susceptibility of Candida species isolated from clinical specimens in central part of Turkey - Ezer, Burak; Ugrakli, Selin; Kasapoglu, Enes (The Journal of Infection in Developing Countries, 2025)
Introduction: This study aimed to examine the distribution and antifungal susceptibility of Candida species in a university hospital and investigate the association of Candida species with age, gender, and clinical specimens. Methodology: A total of 939 samples isolated Candida spp. from various clinical samples between 01.01.2019-06.08.2024 were included in the study. Between 01.01.2019-29.04.2022, Candida species and antifungal susceptibilities were determined using Vitek2 automated system. Between 30.04.2022-06.08.2024, Candida species were detected using the Phoenix automated system and MALDITOF-MS, and antifungal susceptibilities were determined by the gold standard method of broth microdilution. Results: Candida albicans was detected in 511 (54.4%) and non-albicans candida species (NAC) in 428 (45.6%) of the samples with Candida spp. growth. The most frequently detected species were C. albicans in 511 (54.4%) samples, C. parapsilosis in 215 (22.9%) samples, and C. glabrata in 85 (9.1%) samples. The MIC values of all antifungals were statistically significantly higher in NAC species than in C. albicans (p < 0.001). C. tropicalis was isolated most frequently in CSF, C. albicans was isolated most frequently in ocular corneal fluid, C. tropicalis was isolated most frequently in pleural fluid and C. albicans was isolated in all vaginal discharge samples. The higher MIC values of caspofungin, micafungin, and anidulafungin in C. parapsilosis isolates were statistically significant compared to C. albicans and C. glabrata (p < 0.001). Conclusions: Investigating the distribution and antifungal susceptibility of Candida species is vital to initiate appropriate and early empirical antifungal therapy. Each center should determine its species distribution and closely monitor antifungal resistance changes.